2014
DOI: 10.1177/0194599814541629a239
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Tinnitus Pitch and Hearing Loss?

Abstract: Poster PresentationsP213 1, 2, 3, 4 kHz) the preoperative and postoperative air-bone gap were analyzed in order to ascertain whether the preoperative ABG could act as a predictor. Having not passed normality testing, Wilcoxon matched paired signed rank test and Spearman rank coefficient were used for analysis.Results: Throughout the statistical analysis, preoperative ABG correlated most strongly with net difference in postoperative ABG (P < .0001). For each commonly tested frequency assessed this demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thus, studies on human subjects complement these findings. In several recent studies, it was shown that the tinnitus frequency lies within the range of the hearing loss [14][15][16][17]. Furthermore, Dalligna and coworkers report that the tinnitus is directly centered at the frequency of the largest hearing loss [16] and Keppler and coworkers report that there is no correlation between tinnitus pitch and the edges of the impaired frequency ranges [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies on human subjects complement these findings. In several recent studies, it was shown that the tinnitus frequency lies within the range of the hearing loss [14][15][16][17]. Furthermore, Dalligna and coworkers report that the tinnitus is directly centered at the frequency of the largest hearing loss [16] and Keppler and coworkers report that there is no correlation between tinnitus pitch and the edges of the impaired frequency ranges [15].…”
Section: Introductionmentioning
confidence: 99%
“…In several recent studies, it was shown that the tinnitus frequency lies within the range of the hearing loss [14][15][16][17]. Furthermore, Dalligna and coworkers report that the tinnitus is directly centered at the frequency of the largest hearing loss [16] and Keppler and coworkers report that there is no correlation between tinnitus pitch and the edges of the impaired frequency ranges [15]. Nevertheless, there are also some studies reporting a correlation between the edges of the hearing loss and the tinnitus pitch [18][19][20].…”
Section: Introductionmentioning
confidence: 99%